Pengembangan Potensi Desa Di Kecamatan Slahung Dengan Reaktivasi Jalur Exsisting Madiun - Slahung - Zulkarnain, Akbar; Budi, Hari; Priwardana, Faizal Riko (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
Slahung Subdistrict in Ponorogo District, East Java Province, has great potency in agriculture. Most of the crops can not be utilized optimally for economic growth in the Sub-district due to limited access of roads, therefore the study analised development of trains for optimizing the potency of Slahung by using literature study and field survey along the existing route Madiun- Slahung. Data was collected from the Slahung District Office and from a survey of railway conditions along the track. The results obtained are (1) Comparison of energy consumption shows that train is superior at Rp 14, 87 Km / ton and 0.0025 liter / km / ton for freight transport. (2) By utilizing paddy and sugar cane production in Slahung area, Slahung will earn a profit of Rp 2,468,542,182,850.00 per year when selling the crop in Madiun City. (3) The survey estimates that 61% of the Madiun - Slahung railway line in good condition and 39% in poor condition, some of the track located in the middle of agricultural land which will make it easier for farmers to distribute their harvest to the trading center. (4) The survey results show that the Slahung community needs a cheap and fast mode of transportation that overide convenience factor, so that the train with its characteristics can be accepted by the community.